Intrathermocline eddies in the coastal transition zone off central Chile (31–41°S). Issue 10 (2nd October 2013) - Hormazabal, Samuel; Combes, Vincent; Morales, Carmen E.; Correa‐Ramirez, Marco A.; Di Lorenzo, Emmanuel; Nuñez, Sergio
<x xml:space="preserve">Abstract</x> [1] The three‐dimensional structure and the origin of mesoscale anticyclonic intrathermocline eddies (ITEs) in the coastal transition zone (CTZ) off central Chile (31–41°S) were analyzed through the combination of data from oceanographic cruises and satellite altimetry, and the application of an eddy‐resolving primitive equation ocean model coupled with a numerical experiment using a passive tracer. In this region, ITEs are represented by subsurface lenses (∼100 km diameter; 500 m thickness or vertical extension) of nearly homogeneous salinity (>34.5) and oxygen‐deficient (<1.0 mL L−1) waters, properties which are linked to the equatorial subsurface water mass (ESSW) transported poleward by the Peru‐Chile undercurrent (PCUC) in the coastal band. At least five to seven ITEs were observed simultaneously in the area between 31° and 38°S during winter cruises in 1997 and 2009. Satellite data indicated that the ITEs identified from in situ data moved westward, each at a mean speed of ∼2 km d−1 and transported a total volume of ∼1 × 106 m3 s−1 (=1 Sv); the lifespan of each ITE ranged from a few months to 1 year. Model results indicate that ITEs become detached from the PCUC under summer upwelling conditions in the coastal zone.